(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The privatization, globalization and liberalization leading to the tough competition among the industries.Retainment of quality plays the vital role of any industry for to success and profit. Quality practices increases the productivity and efficiency of industries. Hence all the industries irrespective of nature of work are trying to get the quality tag and to follow the Quality Management Systems, that leads to profit and success. Good quality management practices reduces the risk and wastage of materials. The main aim of industries to complete the project within the time with quality. All the industries irrespective of their nature are adopting the International Standards of organization (ISO) as a best Quality Management System. Construction industries also following the Quality requirements for ISO Certification eventhough the nature of work is not uniform. Nowadays ISO becoming a effective Quality tool for the industries. Hence it is needed to study the positive impact of ISO standards on the construction industries. The questionnaires are prepared concentrating the two critical quality factors. The questionnaires are distributed to the industry employees and the responses were collected, and the conclusions are drawn based on the results obtained. An SPSS of Verson 16 used for analysing the data’s. From the results it was observed that the ISO certified industries are good in case of continuous improvement and employees involvement. From the study it was concluded that the ISO implementation does not give a hundred percent quality for the industries. But the ISO certified industries will take relaxed view after getting the ISO certification. The industries which are not certified by the ISO are taking the business very seriously rather than the ISO certified industries. They work towards giving the better quality. It is also observed in the ISO certified industries that the more number of respondents are undecided. This means the employees are free to decide on the benefits or loss due to ISO adoption.. The ISO Certified industries are having marginally better quality than the non - ISO Certified Industries.